2014
DOI: 10.4236/iim.2014.66025
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Multi-Echelon Model for a Sustainable Closed Loop Supply Chain Network Design

Abstract: The integration of entire supply and value chain into a closed loop network is gaining more importance in recent times in order to ensure a business to be economically and environmentally sustainable with the changing trends in business and social environments, growing environmental consciousness in the society and government legislations to protect the environment as well as the business. In this context, this paper considers a multi-echelon closed loop supply chain network design with forward and reverse log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The mathematical model and the meta-heuristic i.e. the hybrid genetic algorithm developed by Aravendan and Panneerselvam [12] [15] are applied in this research work. The case study research method is applied by involving a company from fashion product industries like Footwear industry in South India.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mathematical model and the meta-heuristic i.e. the hybrid genetic algorithm developed by Aravendan and Panneerselvam [12] [15] are applied in this research work. The case study research method is applied by involving a company from fashion product industries like Footwear industry in South India.…”
Section: Methodsmentioning
confidence: 99%
“…They observed that the fashion supply chain systems are characterized by three critical lead-times, which are time-to-market, time-to-serve and time-to-react, which stress the importance of agility in fashion supply networks. Aravendan and Panneerselvam [12] considered a multi-echelon closed loop network design problem with an objective to minimize the total cost of the network and increasing the quality of service. They developed a mixed integer non-linear programming model to solve the CLSCND problem.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…100 The distances between different pairs of facilities or nodes and that of between different pairs of facilities and customers (first customers, second customers) are given in Appendix I. First, the mathematical model developed by Aravendan and Panneerselvam [1] was formulated for the leather goods industry case study using the data shown in Table 1, Table 2 and Appendix I. When it was solved using LINGO15 software, it has been found that the model did not give solution even after several hours of execution.…”
Section: Parameters/variables Valuementioning
confidence: 99%
“…Based on this background of research, the closed loop supply chain model and the suitable algorithm developed by the researchers Aravendan and Panneerselvam [1] [2] are very much in need and would be beneficial for addressing the closed loop supply chain network design problems in the fashion product industries particularly in fashion leather goods industries. To validate and propose the implementation of the model and algorithm developed, the researchers approached few industries that are inclined towards implementing the closed loop supply chain strategies for solving the network design problem of their industries.…”
Section: Introductionmentioning
confidence: 99%